Dimension reduction for −Δ1. (6th February 2014) - Amendola, Maria Emilia; Gargiulo, Giuliano; Zappale, Elvira
Abstract : A 3D-2D dimension reduction for −Δ1 is obtained. A power law approximation from −Δ p as p  → 1 in terms of Γ -convergence, duality and asymptotics for least gradient functions has also been provided.